Physiological causes and consequences of social status in rainbow trout (Oncorhynchus mykiss) - DiBattista, Joseph D (University of Ottawa (Canada), 2005)
A number of social and behavioural traits inherent to the individual are known to influence the outcome of social interactions in salmonid fish. In addition, recent work has raised the possibility that the prior physiological condition of a fish may predetermine its social status. Therefore, the hypothesis that elevated plasma cortisol levels influence social rank was tested, with the prediction that rainbow trout (Oncorhynchus mykiss) treated with cortisol would be relegated to subordinate social status in pairwise contests with an untreated conspecific. Experimental elevation of plasma cortisol significantly increased the probability that the treated fish within each pair became subordinate, an effect later identified as cortisol specific, as it was abolished by simultaneous treatment with the glucocorticoid receptor antagonist, RU486. One possible mechanism through which cortisol could exert this effect was subsequently investigated, namely that cortisol influenced social status through behavioural modifications mediated by changes in brain monoaminergic activity. (Abstract shortened by UMI.)
Keywords: Biology, Animal Physiology.; Agriculture, Fisheries and Aquaculture.